(untitled) (The Batuk, 2020)
This study is based on the impact of HRM practices on organizational performance in terms of behavioral outcomes of financial institutions of Nepal. The variables of HRM practices involve recruitment and selection, training and development, performance appraisal, career planning, compensation, employee participation, and job design whereas variable of behavioral outcomes involve motivation, cooperation, involvement and organizational citizenship. In this study, while analyzing the beta coefficient, it is found that job design sensitivity to organizational performance is high followed by employee participation and compensation system. But all other variables recruitment and selection training and development, and career planning have also positive impact on behaviour outcomes of organizational performance. However, recruitment and selection, training and development, and career planning have minimum impact on behaviour outcomes of organizational performance.